2019
DOI: 10.2147/ijn.s202466
|View full text |Cite
|
Sign up to set email alerts
|

<p>Antioxidative nanofullerol inhibits macrophage activation and development of osteoarthritis in rats</p>

Abstract: Background: There is emerging evidence which suggests that cellular ROS including nitric oxide (NO) are important mediators for inflammation and osteoarthritis (OA). Water-soluble polyhydroxylated fullerene C60 (fullerol) nanoparticle has been demonstrated to have an outstanding ability to scavenge ROS. Purpose: The objective of this study is to assess the effects of fullerol on inflammation and OA by in vitro and in vivo studies. Methods: For in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…Gram-negative bacterial lipopolysaccharide (LPS) has been widely used in previous studies to induce inflammatory mediators. 29 Accordingly, in the present study, HaCaT cells were treated with LPS to establish the in vitro inflammatory OLP model. Initially, we found that after LPS treatment, the miR-23a-3p levels were downregulated significantly in HaCaT cells, which was consistent with the results observed in buccal mucosal tissues of OLP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gram-negative bacterial lipopolysaccharide (LPS) has been widely used in previous studies to induce inflammatory mediators. 29 Accordingly, in the present study, HaCaT cells were treated with LPS to establish the in vitro inflammatory OLP model. Initially, we found that after LPS treatment, the miR-23a-3p levels were downregulated significantly in HaCaT cells, which was consistent with the results observed in buccal mucosal tissues of OLP patients.…”
Section: Discussionmentioning
confidence: 99%
“…The intra-articular injection of fullerenes alone or in combination with HA in surgically induced rabbit models of knee OA showed a dose-dependent fullerene therapeutic effect and synergistic activity with HA [132]. Similarly, fullerol NPs (a polyhydroxylated form of fullerene [133]) showed anti-inflammatory activity in vitro and the ability to prevent synovial inflammation in rat models of OA induced by the intra-articular injection of monoiodoacetate [134]. Carbon nanotubes or graphene-based nanomaterials have also been investigated for OA treatment [135][136][137][138][139]; however, specific studies to target macrophages are lacking.…”
Section: Other Nanomaterial-based Anti-inflammatory Nanoparticlesmentioning
confidence: 97%
“…And it was noticed that innate immune response was in line with the development of OA [ 70 ]. Inhibition of macrophage activation could substantially reduce the inflammatory response and block the OA advancement in rat model [ 71 ]. Given these evidences, we envision that circRNAs are capable of interfering the progression of OA by affecting the innate immune system, which may pave a novel pathway to discover the underlying mechanism of OA.…”
Section: Circrnas In Microenvironment Of Oamentioning
confidence: 99%